The antibacterial activity and mechanism of imidazole chloride ionic liquids on Staphylococcus aureus - Hu, Yanhui; Xing, Yuyuan; Ye, Peng; Yu, Haikuan; Meng, Xianglei; Song, Yuting; Wang, Gongying; Diao, Yanyan (Frontiers in Microbiology, 2023)
ILs (ionic liquids) have attracted emerging interests in the biomedical field due to their unique properties. Despite the varieties of meaningful researches launched in recent years, contemporary advances of ILs applications in the biomedical field and the underlying principles are deficient nevertheless. To identify the antibacterial activity and mechanism of ILs on bacteria, we comparatively evaluated the antimicrobial potency of imidazole chloride ILs (CnMIMCl) on Staphylococcus aureus (S. aureus). The toxicity of ILs was positively correlated to the length of the imidazolidinyl side chain. We selected C12MIMCl to study the mechanism on S. aureus. Through the simultaneous change of internal and external parts of S. aureus, C12MIMCl caused bacteria to be death. The production of large amounts of reactive oxygen species (ROS) within internal parts stimulated oxidative stress, inhibited bacterial metabolism, and led to bacterial death. The external cell membrane could be destroyed, causing the cytoplasm to flow out, and finally the whole cell to be fragmented. The antibacterial effect of C12MIMCl on skin abscess was further verified in vivo of mice.